2018
DOI: 10.1080/02656736.2018.1493541
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety, and efficacy of ultrasound-guided percutaneous microwave ablation for giant hepatic hemangioma

Abstract: (2018) Feasibility, safety, and efficacy of ultrasound-guided percutaneous microwave ablation for giant hepatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…However, giant hemangiomas larger than 5 cm in diameter may cause compression symptoms, such as obstructive jaundice, gastric outlet obstruction, and Budd-Chiari syndrome, or coagulopathy (Kasabach-Merritt syndrome) requiring further intervention [10] . The current treatments include surgery, interventional therapy [3] , radiofrequency and microwave ablation [4] . TAE is a common method used for the treatment of hepatic hemangioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, giant hemangiomas larger than 5 cm in diameter may cause compression symptoms, such as obstructive jaundice, gastric outlet obstruction, and Budd-Chiari syndrome, or coagulopathy (Kasabach-Merritt syndrome) requiring further intervention [10] . The current treatments include surgery, interventional therapy [3] , radiofrequency and microwave ablation [4] . TAE is a common method used for the treatment of hepatic hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…With the deepening of the concept of minimally invasive and rapid rehabilitation, exploring the minimally invasive treatment of hepatic hemangioma is a hot topic. In recent years, there have been many studies on interventional therapy [3] and ablation of hepatic hemangioma [4] . However, the safety and effect of interventional therapy and ablation on hepatic hemangioma need to be con rmed by further study [5] .…”
Section: Backgroudmentioning
confidence: 99%
“…In all the 17 studies, reviewed diagnosis of HH was confirmed by imaging based on the typical enhancement pattern on contrast-enhanced CT, MR or contrast-enhanced ultrasound (CEUS). In one study by Wang et al, preprocedural blood tests were performed to exclude malignant neoplasm (AFP, CEA and CA19-9) [15]. Indication to resort to ablative percutaneous strategies were mostly homogeneous among the considered studies, including the presence of "large/giant" HH associated to persistent-related symptoms in patients refusing open or laparoscopic surgical resection.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In 4 out of 17 studies, authors performed preprocedural peritoneal saline infusion (hydrodissection) to provide a satisfactory sonographic window and to protect nontarget structures (diaphragm, abdominal wall, colon, gallbladder) while ablating lesions abutting the Glisson capsule or the diaphragm [15,17,[23][24][25].…”
Section: Ablation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation